The Impact of Financial Inclusion on Public Financial Services Education through Financial Technology in Sleman Regency, Indonesia - I Made Laut Mertha Jaya (Esensi: Jurnal Bisnis dan Manajemen, 2019)
The purpose of this study is to know the impact of financial inclusion on public financial services education through financial technology. This research was conducted in Sleman Regency because the area was quite large in Yogyakarta, and was ranked third. This type of research is quantitative research. Data collection methods used are questionnaires and literature studies. Data analyses used in this study are the validity test, reliability test, descriptive statistical test, and SEM (Structural Equation Modeling) analysis test. The results of this study found that financial inclusion has been proven to have no impact on public financial services education. However, financial inclusion has proven to have a significant impact on financial technology in Sleman Regency in 2018. In addition, financial inclusion through financial technology has also proven to have a positive impact on public financial service education in Sleman Regency in 2018.